Examining fractal image processing and analysis - Nayak, Soumya Ranjan 1984-; Mishra, Jibitesh (IGI Global, 2020)
"This book examines the recent trends and applications of fractal image analysis and processing such as box-counting analysis, multi-fractal analysis, 3D fractal analysis, chaos theory, texture analysis, color imaging, and pattern recognition"--